Biomechanical performance diagnostics: concepts and applications in ski-jumping - Fritz, J.; Kröll, J.; Schwameder, H. (ISBS Proceedings Archive (Michigan), 2018)
This paper presents an overview regarding the evaluation of existing biomechanical measurement methods and their practicability in biomechanical performance diagnostics (BPD) in ski-jumping. Depending on the purpose of the BPD different biomechanical measurement systems have been developed and applied. Force plates as well as pressure insoles are used to assess the kinetics during hill jumps and dry land exercises. Based on an inverse dynamics approach, ground reaction forces can be calculated during take-off using the kinematic information in conjunction with the body segment parameters. Inertial measurement units provide the opportunity to determine the orientation of the skis during flight. Easy handling, low interference with the athlete and the ability to give immediate feedback are the requirements for a measurement system in order to enable an effective BPD setting.